(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research article seeks to bring forth the outcome of partition on the Indian Sub-Continent after India gained its independence in 1947 after the long rule of British colonization. It manifests how the colonizers sowed the seeds of hatred which led not only to unprecedented deaths and devastation but also the process of division of the Sub-Continent on communal and sectarian lines. The independence gave the two countries government systems with destroyed economies and a system without any establishment and experience. More than fifteen million refugees were forced to go to regions completely foreign to them. The hatred, communal riots between Hindus / Sikhs and Muslims completed the mission which demanded blood and human lives. Khushwant Singh’s "Train to Pakistan" is an excellent and realistic story of political hatred, violence and communal riots during those chaotic and critical days that preceded and followed the partition of India. It tells the miserable tales of individuals and communities that were caught in the whirl of partition. Millions of people on both sides of the border who had been, like their ancestors, born and brought up on the same soil were forced to move only because they worshipped one God and not the other and here comes the question how communalism was one of the major aspects of the partition of India. Originally it is entitled Mano Majra which indicates static, while the present title "Train to Pakistan" suggests change. This maybe the reason that VA Sahane remarked that the change of the title of the novel from “Mano Majra” to “Train to Pakistan” is in keeping with the theme of the novel. This study will try to look at the aspects of postcolonial anxiety, national identity and how these are related to an understanding of the political-historical fact of the partition.